The Role of Parents in Providing Nutritious Food to Prevent Stunting in Early Childhood - Yanti, Nursaida; Nofianti, Rita (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study explores the role of parents in providing nutritious food to prevent stunting in early childhood. Stunting, a condition caused by chronic malnutrition, affects children's growth, cognitive development, and overall health. Using a literature review method, this research analyzes findings from various scholarly sources to examine parental involvement in ensuring a balanced diet. The results highlight that parents, especially mothers, play a crucial role as educators, facilitators, and role models in children's nutrition. Providing a balanced diet rich in carbohydrates, proteins, fats, vitamins, and minerals, as well as promoting healthy eating habits, is essential in preventing stunting. Additionally, parents should actively monitor children's growth through posyandu (community health services) and engage in nutrition education programs. The study concludes that strong parental awareness and commitment significantly contribute to reducing stunting rates. Future research should focus on effective interventions and policies to enhance parental participation in early childhood nutrition.